Tinjauan Literatur Perbandingan Internasional atas Asuransi Wajib Kendaraan Bermotor : Pelajaran bagi Indonesia - Pristiwanto Bani (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to analyse the trends and best practices of compulsory motor vehicle insurance in various countries as a lesson for Indonesia. The method used is literature observation with the traditional literature review method of articles published in international journals and practices that have been carried out by several selected countries, namely England, Germany, Kenya, India, Japan, the United States, Malaysia, Singapore and Australia. The results of the analysis show findings that most countries implement a compulsory motor vehicle insurance system. This insurance aims to provide financial protection to accident victims and encourage legal compliance among vehicle owners. Although this policy has provided significant benefits, such as reducing the financial burden on victims and more efficient dispute resolution, challenges such as high premiums, the complexity of the claims process, and uninsured vehicles still need to be overcome. The application of digital technology, including blockchain, is expected to increase transparency and efficiency in the claims process. Thus, this article highlights the importance of continuous improvement in the compulsory insurance system to ensure fair and effective protection for all parties involved. Based on these international practices, several recommendations for Indonesia include: strengthening mandatory insurance regulations, implementing technology in the insurance management system, increasing public insurance literacy, and developing policies that anticipate the emergence of autonomous vehicles. This study highlights the importance of learning from international experiences in developing an effective and sustainable compulsory motor vehicle insurance system in Indonesia.